PENGARUH PENDAPATAN KELUARGA, PENDIDIKAN ISTRI, DAN USIA KAWIN PERTAMA TERHADAP PENGGUNAAN KONTRASEPSI PADA WANITA USIA SUBUR DI KOTA PEKANBARU - Mardhotillah Ayu; Maulida Yusni; Aulia Fahda Ando (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the family income, education of wives and age at first marriage on contraceptive use in fertile aged women in Pekanbaru City. This research is a primary research which data collection using a research questionnaire. The total population of the study was all users of active contraceptives in Pekanbaru City as many as 321,274 people, then based on the Taroyamane formula with a level of 10%, a total sample of 100 respondents was obtained. The analytical method used is descriptive quantitative using multiple linear regression analysis. Based on the results of the study, it is known that family income, wife's education and age at first marriage have an effect on the use of contraceptives in women of childbearing age in Pekanbaru City together or simultaneously. However, partially the variables of family income and wife's education have a significant positive effect on contraceptive use among women of childbearing age in Pekanbaru City. However, age at first marriage did not have a significant effect on contraceptive use in women of childbearing age in Pekanbaru City. Family income is the dominant factor affecting contraceptive use in women of childbearing age in Pekanbaru City.Keywords: family income, wife's education, age at first marriage, contraception use